Pelatihan Penggunaan Canva Untuk Menciptakan Media Pembelajaran Interaktif Bagi Guru dan Siswa di SDN Sukosari Kota Madiun - Pamungkas, Ridho; Setiawan, Dimas; Lenawati, Mei; Asnawi, Noordin (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2024)
The utilization of technology in education is one of the important steps in improving the quality of learning in Indonesia, especially in primary schools. Along with technological developments, the use of graphic design applications such as Canva can increase teacher creativity in creating interesting and interactive learning media. SDN Sukosari, Madiun City, is the chosen location to implement training on the use of Canva for teachers to improve the quality of learning. The problem faced by teachers at SDN Sukosari is the limited ability to create learning media that is interesting and in accordance with the characteristics of students. Therefore, this training aims to improve teachers' skills in using Canva to design interactive learning media. The method used in this service is practical training with a hands-on approach involving 8 teachers at SDN Sukosari. The results showed that 90% of teachers felt more confident in using Canva, and 85% of students felt that learning became more interesting. The results of this service show that the use of Canva can improve the quality of teaching and learning at the primary school level, and provide a basis for the development of technology-based learning in the future.